Arahan Penataan Promenade Setu Babakan - Edwina Fernanda; Weishaguna (UPT Publikasi Ilmiah Unisba, 2023)
Abstract. Arrangement directions need to be carried out in overcoming the lack of direction in structuring the promenade at Setu Babakan. The urgency of this research is based on the existence of an interest in policy urgency, urgency in Islamic values, and urgency of real problems. The existence of this problem makes an impetus in the emergence of a goal, namely the direction of a better promenade arrangement. The theory that is used as a reference for arranging this promenade uses the waterfront theory which has Betawi characteristic ornaments. The approach method taken is qualitative with data collection methods namely primary (field observations and interviews) and secondary (literature study). The analytical method used is comparative analysis, namely making comparisons between the existing conditions and the design principles of the waterfront area which are assessed based on the criteria. Based on the results of the analysis, it results that there is a different assessment between the existing conditions and the criteria applied in the design principles of the waterfront area so the direction for the arrangement of the Setu Babakan promenade is needed to become a recommendation for the direction of the arrangement. Abstrak. Arahan penataan perlu dilakukan dalam mengatasi kurangnya arahan dalam penataan promenade di Setu Babakan. Urgensi penelitian ini didasari pada adanya kepentingan dalam urgensi kebijakan, urgensi dalam nilai islam, dan urgensi masalah nyata. Adanya permasalahan ini menjadikan suatu dorongan dalam munculnya suatu tujuan yakni adanya arahan penataan promenade yang lebih baik. Teori yang dijadikan sebagai acuan untuk menata promenade ini menggunakan teori waterfront yang terdapat ornamen ciri khas Betawi. Metode pendekatan yang diambil yakni secara kualitatif dengan metode pengumpulan data yakni secara primer (observasi lapangan dan wawancara) dan sekunder (studi literatur). Metode analisis yang digunakan yakni analisis komparasi yaitu melakukan perbandingan antara kondisi eksisting dengan prinsip perancangan kawasan tepi air yang dinilai berdasarkan kriterianya. Berdasarkan hasil analisis menghasilkan bahwa terdapat penilaiannya yang berbeda antara kondisi eksisting dengan kriteria yang diterapkan dalam prinsip perancangan kawasan tepi air, sehingga adanya arahan penataan promenade Setu Babakan diperlukan untuk menjadi rekomendasi arahan penataan.